Financial Crisis and Leverage Determinants : A Juxtaposition of Pre and Post-Crisis Periods Using HLM - Singh, Amit Kumar; Bansal, Preeti (Indian Journal of Finance, 2022)
The present study examined the direct and indirect influences of firm-level and industry-level determinants on capital structure for all BSE-listed firms in India. The study analyzed financial data from 2000 – 2019 and employed the hierarchical linear modeling technique of regression as firms are a subset of industries. The output demonstrated that a few capital structure determinants either did not have any impact or had the same effect in both pre and post-crisis periods. However, a few determinants such as short-term liquidity, firm profitability, and Z - score had a conflicting impact on leverage in the two time periods. Determinants such as median industry tangibility, median industry leverage, industry munificence, industry liquidity, and industry dynamism had a significant impact in one period and an insignificant impact in another period. This showed that the direct effect of capital structure determinants changed when equity market and credit supply conditions varied. We showed that industry-level factors moderated the relationship between leverage and firm-level factors. Further, it was exhibited how economic conditions affected not just the direct influences of firm and industry level factors but also the indirect influences of industry-level factors. The results of the present study highlighted the complexity of corporate leverage decisions by exhibiting how changes in economic conditions and industry characteristics led to changes in leverage levels.